Determination of the Flow Angle in Hydraulic Components - Günther, Lennard; Osterland, Sven; Weber, Jürgen (International Journal of Fluid Power, 2024)
The paper presents a general analytical equation for the determination of the flow angel in hydraulic components like valves and pumps. Exemplary, the method is applied to two different valve concepts – a cartridge valve and a rotary slide valve. cos(εavg)=1/2(cos(αl)−cos(αr)) The huge advantage of this equation is the simple expression with no dependencies on operation conditions. Only the geometry is important. The underlying phenomenon is valid for turbulent flows. Thus it is useable for almost all hydraulic applications. It makes it possible to predict the flow force as well as to optimize the flow geometry. It describes the flow angle of the free jet behind a narrow section (e.g. a control edge of a valve). By a suitable choice of the angle of the free jet, the flow force can be reduced by changing the direction of the outgoing impulse. With regard to cavitation, the impact of the free jet can be shifted and thus the cavitation erosion can be shifted or weakened. This paper deals with the investigation of the flow angle of free jets as well as the prediction of the flow force in valves without CFD. For the illustration a cartridge and a rotary slide valve are used as technical applications. In the first section, geometric factors influencing the flow angle are discussed, as well as the transferability of the results under varying operating conditions (laminar and turbulent). Using a generic minimal model, the behaviour of the flow angle with respect to geometric influence factors and operating conditions is investigated by means of CFD. The results are adapted to real applications in the second section. The direct adjustment of the flow angle results in a significant improvement in the characteristic behaviour of the presented valves (such as flow force and resistance torque). It becomes clear how efficient the adjustment of the flow angle can be if the basis of the formation of the free jet is known. Due to the derivation of the relationship with the help of an abstracted minimal model, the knowledge gained can be used in many ways and can also be transferred to other applications in the field of fluid technology. Optimization processes are more efficiently without using elaborated simulation models e.g. driven by CFD.